Approche des relations entre la croissance de l'huître Crassostrea gigas et le milieu dans le bassin d'Arcachon - Maurer, Daniele (1989)
study of the experimental growth of the oyster Crassostrea gigas was undertaken of 1985 to 1988, parallel to a follow-up hydrobiologic of the medium, in three sites of the basin of Arcachon. - The characteristics of growth of the studied sites proved very stable during various years they are also very different from one site to another, the performances being able to vary the simple one with the double of the center of the basin towards the exit on the ocean. It is during the summer and of the autumn that the difference is established between the sectors, the spring growths being similar. The hierarchy observed is associated a more or less great precocity of the laying. - A gradient influences continental oceanic-influence is observed, resulting in more extreme conditions in the internal zones of the basin for the parameters temperature and salinity. There is not, on the other hand, of gradient net of phytoplanctonic richness. The seasonal structure is very marked and strongly dominant on the geographical and interannual structures, in spite of very contrasted years and heterogeneous sites as for the water masses which bathe them and with the performances of growth of molluscs in breeding in these sectors. The worse growth of the internal sectors could comparison with their conditions of medium more unstable and more extremes, which would cause an energy demand of molluscs quite higher than that of the best zones. In period of not very abundant food, it would result a limitation from it from the growth. Une étude de la croissance expérimentale de l'huître Crassostrea gigas a été menée de 1985 à 1988, parallèlement à un suivi hydrobiologique du milieu, en trois sites du bassin d'Arcachon. - Les caractéristiques de croissance des sites étudiés se sont avérées très stables au cours des différentes années; elles sont aussi très différentes d'un site à l'autre, les performances pouvant varier du simple au double du centre du bassin vers la sortie sur l'océan. C'est au cours de l'été et de l'automne que la ...